1997
DOI: 10.4315/0362-028x-60.9.1105
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Preparers' Food-Safety Knowledge and Practices Following Widely Publicized Outbreaks of Foodborne Illness

Abstract: There has been extensive media coverage of the Pacific Northwest outbreak of foodborne illness caused by Escherichia coli O157:H7 in 1993 and continuing smaller incidences of both E. coli and salmonella transmission by food. An increase in consumer awareness and knowledge of microbial food safety was expected as a result. A telephone survey of Oregon food preparers (using a random-digit-dialing household sample) in December 1995 and January 1996 revealed that knowledge about foodborne illness was greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…Fig. 1) It is not clear how knowledge affects practice in this sample, but other surveys, regardless of ethnic mix, found that level of education is related to food safety knowledge scores (Altekruse et al, 1999;Meer & Misner, 2000;Williamson et al, 1992;Woodburn & Raab, 1997). However, not understanding the role of pathogenic bacterial in foodborne illness or that their hands could be the source of pathogenic bacteria could lead to unsafe practices.…”
Section: Focus Groupsmentioning
confidence: 80%
See 1 more Smart Citation
“…Fig. 1) It is not clear how knowledge affects practice in this sample, but other surveys, regardless of ethnic mix, found that level of education is related to food safety knowledge scores (Altekruse et al, 1999;Meer & Misner, 2000;Williamson et al, 1992;Woodburn & Raab, 1997). However, not understanding the role of pathogenic bacterial in foodborne illness or that their hands could be the source of pathogenic bacteria could lead to unsafe practices.…”
Section: Focus Groupsmentioning
confidence: 80%
“…Based on information from the direct observations and adapting some questions from relevant literature (Altekruse, Yang, Timbo, & Angulo, 1999;Angelillo, Foresta, Scozzafava, & Pavia, 2001;Bruhn & Schutz, 1999;Fein, Jordan Lin, & Levy, 1995;Meer & Misner, 2000;Unklesbay, Sneed, & Toma, 1998;Williamson, Gravani, & Lawless, 1992;Woodburn & Raab, 1997), a survey instrument (available upon request) addressing knowledge, attitudes and norms pertaining to mushroom food safety issues was developed to be completed in individual face-to-face interviews. To assure content validity, seven individuals with expertise in food safety and food microbiology reviewed the draft instrument.…”
Section: Interview Instrumentmentioning
confidence: 99%
“…Epidemiological data from different parts of the globe have shown that a significant proportion of foodborne illnesses are attributable to improper food processing practices in consumers' homes (Redmond & Griffith, 2003). Food can be mishandled at many places during food preparation, handling and storage (Knabel, 1995;Worsfold & Griffith, 1995) and several studies indicate that consumers have inadequate knowledge about procedures needed to prevent foodborne illnesses at home (Altekruse, Street, Fein, & Levy, 1996;Knabel, 1995;Mederios, Hillers, Kendall, & Mason, 2001;Meer & Misner, 2000;Redmond & Griffith, 2003;Woodburn & Raab, 1997). The prevention of foodborne illnesses requires educating food consumers on safe food handling practices (Jev snik, Hlebec, & Raspor, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…As a consequence, food-safety objectives are now being set at the moment of consumption rather than at the moment of purchase (WHO/FAO, 2004) with consumers being heralded as the essential final link in the food chain to ensure safe food consumption and avoid food-borne disease (The Pennington Group, 1997, as cited in Redmond et al, 2004). This shift in focus has allowed researchers to comprehensively examine domestic food preparation practices using telephone surveys (Cody & Hogue, 2003;Redmond & Griffith, 2004a;Woodburn & Raab, 1997), postal surveys (Angell, 2008;Dharod et al, 2004;Redmond & Griffith, 2005a;Redmond & Griffith, 2005b;Redmond & Griffith, 2006a;Takeuchi et al, 2005a;Takeuchi et al, 2005b;Williamson et al, 1992), online surveys (Byrd-Bredbenner et al, 2007;Nauta et al, 2008;Unusan, 2007), home visits (Worsfold & Griffith, 1996), observations (Anderson et al, 2004;Clayton et al, 2003;Fischer, A. et al, 2007;Jay et al, 1999;Redmond & Griffith, 2006b;Redmond et al, 2004), laboratory simulations (Meredith et al, 2001) and reviews (Redmond & Griffith, 2003;Sattar et al, 1999;Wilcock et al, 2004).…”
Section: Introductionmentioning
confidence: 99%